Enhanced neutralising antibody response to bovine viral diarrhoea virus (BVDV) induced by DNA vaccination in calves. Issue 32 (31st July 2015) - R. El-Attar, Laila M.; Thomas, Carole; Luke, Jeremy; A. Williams, James; Brownlie, Joe
Highlights Co-expression of a RIG-I agonist with BVDV viral antigen could enhance DNA vaccine potency in cattle. Integration of RIG-I agonist greatly enhances BVDV neutralising antibody response. BVDVE2 protein augments antibody response to NS3 in BVDV DNA vaccine.